ESP Students’ Experiences and Challenges in Using Edmodo - Ferdian, Nurizzi Rifqi; Putri, Dwi Diana; Febrianingrum, Lasmi (PANYONARA: Journal of English Education, 2022)
Following the trend of ICT in teaching and learning English, many higher education institutions have an intention to lead the students into a digital environment by using Edmodo as an online platform. This study investigates ESP (English for Specific Purposes) studentsâ€™ experiences and challenges in using Edmodo. The data from this study were collected using questionnaires shared with 120 students and focus group discussions volunteered by ten students. The study revealed that the students frequently used Edmodo to help their academic achievement (xÌ„=3.63). They also regularly felt comfortable using Edmodo as their learning circumstances (xÌ„=3.61), and they occasionally had a problem using Edmodo (xÌ„=3.14). The focus group interview discovered that the use of Edmodo can motivate them to learn English since it is an effective tool that can be accessed everywhere and anytime, especially for doing assignments and quizzes, communicating with one another, and collaborating with students from other schools or countries. Moreover, although they did not find any difficulties using Edmodo, they were worried about answering the questions in quizzes and assignments because they might make typos, incomplete sentences, or incorrect answers. Importantly, the result can be expanded into online learning circumstances to a new standpoint that can efficiently manage virtual activities in learning English using Edmodo. For further work, it is recommended to investigate the studentsâ€™ experiences and challenges of other e-learning platforms and their impact and motivation for the student’s academic performances.